Mechanism-based therapies for heart failure and cardiac arrhythmias - Marks, Andrew (Henry Stewart Talks, 2007)
Introduction to excitation-contraction coupling, History of the field of EC coupling, Introduction to the ryanodine receptor/calcium release channel (RyR2), Mechanisms that regulate the RyR2 channel during stress, Defective regulation of RyR2 in heart failure, Evidence that diastolic sarcoplasmic reticulum (SR) calcium leak causes heart failure and arrhythmias in vivo, Novel therapeutic approaches to treating heart failure and preventing sudden cardiac death by fixing the leak in RyR2 channels